2023
DOI: 10.3390/app13053059
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Accurate Real-Time Vehicle Detection Method Using Deep Learning for Unconstrained Environments

Abstract: Deep learning-based classification and detection algorithms have emerged as a powerful tool for vehicle detection in intelligent transportation systems. The limitations of the number of high-quality labeled training samples makes the single vehicle detection methods incapable of accomplishing acceptable accuracy in road vehicle detection. This paper presents detection and classification of vehicles on publicly available datasets by utilizing the YOLO-v5 architecture. This paper’s findings utilize the concept o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Here 43,52 have lowest ranks. In rain situation our method produces best results followed by 57,45,48,50,51 . Here 52 has lowest rank.…”
Section: Evaluation Criteriamentioning
confidence: 89%
“…Here 43,52 have lowest ranks. In rain situation our method produces best results followed by 57,45,48,50,51 . Here 52 has lowest rank.…”
Section: Evaluation Criteriamentioning
confidence: 89%
“…Faris et al [ 115 ] proposed a Yolo-v5 architecture vehicle detector using the techniques of transfer learning on publicly available datasets, namely, PKU, COCO, and DAWN. The experimental result showed that the proposed model achieved a state-of-the-art in the detection of various vehicles.…”
Section: Application Of Dcnn For Vehicle Detection and Classificationmentioning
confidence: 99%
“…WANG et al [8] proposed the YOLOv5-NAM algorithm, which added the NAM attention module and proposed methods for tracking small target vehicles, embedding the feature extraction process into the joint training of the prediction head. Moreover, Farid et al [9] enhanced the accuracy of vehicle detection by modifying YOLO weights and utilizing transfer learning. Nitika et al [10] employed a region-based convolutional neural network to detect moving vehicles both during the day and at night, optimizing the detection performance under different weather conditions.…”
Section: Introductionmentioning
confidence: 99%